Formal methods : foundations and applications : 19th Brazilian Symposium, SBMF 2016, Natal, Brazil, November 23-25, 2016, Proceedings /: foundations and applications : 19th Brazilian Symposium, SBMF 2016, Natal, Brazil, November 23-25, 2016, Proceedings. (2016) - Unknown
No abstract available